Bending of rectangular plates with large deflections - Wang, Chi-Teh (National Advisory Committee for Aeronautics, 1948)
This document presents the solution of Von Karman equations for thin plates with large deflections for special cases of rectangular plates of 1.5 and 2.0 length-width ratios under uniform normal pressure. The boundary conditions approximate panels with riveted edges under normal pressure greater than that of the surrounding panels. Center deflections (to twice the plate thickness), membrane stresses, and extreme-fiber bending stresses are given as functions of the pressure. For small deflections, the results are consistent with those given by Timoshenko.
"April 1948."
NACA TN No. 1462.
Keywords: Plates (Engineering); Bending.; Strains and stresses.; elektronické knihy; electronic books